Relationship between echocardiographic characteristics and cardiac biomarkers during long-distance trail running - Jouffroy, Romain; Hergault, Hélène; Antero, Juliana; Vieillard Baron, Antoine; Mansencal, Nicolas (Frontiers in Cardiovascular Medicine, 2022)
Background Even if the beneficial cardiovascular effects of moderate exercise are recognized, effects of prolonged and intense exercise are still debated. This study aims to detect cardiovascular changes associated with long endurance running by assessing the relationship between echocardiographic parameters and cardiac biomarkers during long-distance trail running. Methods We performed a prospective observational study that included 20 participants who were all amateur runners (median age of 41 years old, still alive after a 7-year clinical follow-up) from 80-km trail running. All the participants underwent an echocardiographic examination and venous blood sampling before the race, at the intermediate refreshment checkpoints of the race (21st and 53rd km), and within 10 min after arrival. Results Mitral E/A velocity ratio and mitral TDI e’ wave were significantly decreased at the 21st km to arrival (p < 0.05). Mitral S wave and global longitudinal strain (GLS) were significantly decreased from the 53rd km to arrival (p < 0.05 for 53rd and 80th km). As compared to baseline, T-troponin and NT-proBNP were significantly increased at the 21st km in all the participants, but T-troponin values were systematically increased above the significative threshold. Diastolic echocardiographic abnormalities were mainly observed among participants with highest NT-proBNP (> 77 ng.l–1) values at the 21st km. As compared to baseline, mitral e’ wave was significantly decreased (–35%) in participants with highest values of NT-proBNP. Similarly, GLS was also depressed among participants with highest troponin values at the 53rd km (p = 0.01 for 53rd km and p = 0.04 for arrival). Conclusion During the long-distance trail running, the early LV decrease in diastolic echocardiographic parameters is associated with increase in NT pro-BNP blood levels, and the decrease in LV systolic echocardiographic parameters later is associated with increase in T-troponin blood levels.